Effect of Different Bend Pipes on the Propagation Characteristics of Premixed Methane-Air Explosion in Confined Spaces. (26th February 2021) - Qiu, Jinwei; Jiang, Bingyou; Tang, Mingyun; Zhou, Liang; Ren, Bo
Abstract : To explore the effect of different bend pipes on the propagation characteristics of premixed methane-air explosion, the experimental explosion pipe system and numerical model were established. By adopting the comparative analysis of experiments and numerical modeling, it conducted researches on the overpressure evolution of gas explosion shock wave in pipes with different bends and obtained the expressions of attenuation coefficient of shock wave overpressure. The results showed that the change of pipe direction accelerated the attenuation of gas explosion shock wave. The propagation attenuation of gas explosion in the bend pipe was mainly affected by the bending angle and initial peak overpressure before bending. With the increase of the bending angle, the attenuation coefficient of gas explosion shock wave gradually increased. For the same bending angle, the attenuation coefficient of gas explosion shock wave increased with the increase of gas volume. The obtained coupling relationships between attenuation coefficient, bending angle, and initial peak overpressure before bending were useful for estimating the overpressure value after the bend. The results presented in this paper have important significance for the assessment of structures that have been damaged in the mine laneway of gas exploration accidents, further enriching the gas exploration spread theory.